Hippocampal MRI volumetry in cognitively discordant monozygotic twin pairs. Issue 1 (5th January 2004) - Järvenpää, T; Laakso, M P; Rossi, R; Koskenvuo, M; Kaprio, J; Räihä, I; Kurki, T; Laine, M; Frisoni, G B; Rinne, J O
Abstract : Objective: To investigate whether hippocampal atrophy, a proxy for incipient Alzheimer's disease, can be detected in non-demented monozygotic co-twins of demented twins by using volumetric magnetic resonance imaging (MRI). Methods: Seven pairs of monozygotic female twins discordant for cognitive function (mean (SD) age 75 (4) years), and 10 age and education matched healthy controls (seven women, three men; mean age 73 (3) years) were studied with volumetric MRI. Results: The mean normalised right hippocampal volume was 31% lower (p = 0.002) in the demented twins, and 6% lower (p = 0.45) in the non-demented twins than in the controls. In the left hippocampus, the mean normalised volume was 36% lower (p<0.001) in the demented twins, and 9% lower (p = 0.13) in the non-demented twins than in the controls. Conclusions: Significant hippocampal atrophy was detected in the demented twins compared with the controls. This is in line with previous imaging and pathological studies, with hippocampus showing the early changes in Alzheimer's disease. In the non-demented twins, only a minor, non-significant reduction was observed in the hippocampal volumes compared with the controls. This could reflect gene–environment interactions that have protected the non-demented twins longer than their demented co-twins and contributed to the relative preservation of their hippocampal volumes, or it could be a sign of preclinical Alzheimer's disease in the non-demented twins.